Depression and anxiety in cervical degenerative disc disease: Who are susceptible? - Sang, Dacheng; Xiao, Bowei; Rong, Tianhua; Wu, Bingxuan; Cui, Wei; Zhang, Jianhao; Zhang, Yue; Liu, Baoge (Frontiers in Public Health, 2023)
Background. Preoperative depression and anxiety are associated with poorer patient-reported outcomes following cervical spine surgery. Identification of and interventions for these disorders are key to preventing related negative effects. However, most spine surgeons do not routinely evaluate mental health disorders. Few studies have investigated which patients with cervical degenerative diseases (CDD) are susceptible to depression and anxiety. Objective. To determine the factors associated with depression and anxiety in patients with CDD. Methods. 312 patients with CDD were recruited in this cross-sectional case-control study. Patients underwent a structured interview to acquire demographic and clinical characteristic information, which included the Neck Disability Index (NDI), modified Japanese Orthopaedic Association (mJOA), and Visual Analog Scale (VAS) for neck/arm pain. Depression and anxiety were evaluated using the Zung Self-Rating Depression and Anxiety Scales. Univariate and multivariate logistic regression analyses were used to identify factors associated with depression and anxiety. Results. Of all patients, 102 (32.7%) had depression and 92 (29.5%) had anxiety. 206 (66.0%) patients with neither depression nor anxiety were defined as the control group. Univariate analysis indicated that gender, educational level, occupation type, Charlson comorbidity index, symptom duration, symptomatology, surgery history, NDI, mJOA, VAS-neck, and VAS-arm scores were associated with depression and anxiety (except for symptom duration for anxiety). Multivariate logistic regression analysis indicated that females (odds ratio [OR] 1.81, 95% confidence interval [CI] 1.01–3.23), physical work (OR 2.06, 95% CI 1.16–3.65), poor mJOA score (ORmoderate 2.67, 95% CI 1.40-5.07; ORsevere 7.63, 95% CI 3.85- 15.11), and high VAS-neck score (OR 1.24, 95% CI 1.11–1.39) were independent risk factors for depression. Physical work (OR 1.84, 95% CI 1.01–3.35), poor mJOA score (ORmoderate 2.66, 95% CI 1.33-5.33; ORsevere 9.26, 95% CI 4.52-18.99), and high VAS-neck score (OR 1.34, 95% CI 1.19–1.51) were independent risk factors for anxiety. Conclusion. Approximately one-third of patients with CDD had depression or anxiety. Patients who engaged in heavy work and had severe symptoms (poor mJOA and high VAS-neck scores) are susceptible to depression and anxiety. Additionally, female patients are susceptible to depression. Our findings may help identify CDD patients with depression and anxiety in clinical practice.